Fabrication and properties of PZT-ordinary Portland cement composites - A. Chaipanich (2018)
Lead zirconate titanate (PZT)-ordinary Portland cement (OPC) composites were fabricated using 40%, 50% and 60% of PZT by volume. The dielectric constants of the composites were found to be 139, 176 and 290 for composites containing 40%, 50% and 60% PZT respectively. Successful poling of the composites was achieved and the measured piezoelectric coefficient (d33) of the composites increased with PZT content. Measured d33values for the composites with 50% and 60% PZT content were 26 and 42 pC/N respectively. These are very promising results with very high d33values for PZT-cement composites. Moreover, using this fabrication method it is possible to produce PZT-OPC composites with more than 50% PZT by volume and that these composites have good potential for use in structural applications. © 2007 Elsevier B.V. All rights reserved.